PENGEMBANGAN MODUL METODE PROYEK UNTUK MENGETAHUI KETERAMPILAN PROSES SAINS (KPS) SISWA PADA LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - irma zarwinda zarwinda (UIN AR-RANIRY, 2019)
This study was conducted to develop a project method module on the subject of electrolyte and non – electrolyte solution, to assess the quality of the module based on the experts suggestions, to get the teacher and student responses to the project method module, and know the KPS based student learning styles and the role project method module. The study was conducted in three schools in Banda Aceh (SMA Negeri 11, SMA Negeri 10 Fajar Harapan, and SMA Negeri 5 Banda Aceh) by using quantitative research with research methods of and development (R and D). The design of this study is Pre-test and Post-test Group. Experts assessment for the quality of module shows a score of 4.21 (good), the results showed that 90.67% teachers and 80.68% students responded positively to the module. Hypothesis testing is done toward the pretest and posttest data based on students from three schools with a significant level of 0.05%. The result from pretest data using Mann-Whiteney (U test) have a few different although it did not differ significantly. The result from posttest data using the t test are not significantly. The role of the modul was based on the seen average value of students KPS posttest in three schools which is 72.19 with the criteria of